X-ray variability of the HMXB Cen X−3: evidence for inhomogeneous accretion flows. Issue 4 (26th December 2020) - Sanjurjo-Ferrín, G; Torrejón, J M; Postnov, K; Oskinova, L; Rodes-Roca, J J; Bernabeu, G
ABSTRACT: Cen X−3 is a compact high-mass X-ray binary likely powered by Roche lobe overflow. We present a phase-resolved X-ray spectral and timing analysis of two pointed XMM–Newton observations. The first one took place during a normal state of the source, when it has a luminosity L X ∼ 10 36 erg s −1 . This observation covered orbital phases ϕ = 0.00–0.37, i.e. the egress from the eclipse. The egress light curve is highly structured, showing distinctive intervals. We argue that different intervals correspond to the emergence of different emitting structures. The light-curve analysis enables us to estimate the size of such structures around the compact star, the most conspicuous of which has a size ∼0.3 R *, of the order of the Roche lobe radius. During the egress, the equivalent width of Fe emission lines, from highly ionized species, decreases as the X-ray continuum grows. On the other hand, the equivalent width of the Fe K α line, from near-neutral Fe, strengthens. This line is likely formed due to the X-ray illumination of the accretion stream. The second observation was taken when the source was 10 times X-ray brighter and covered the orbital phases ϕ = 0.36–0.80. The X-ray light curve in the high state shows dips. These dips are not caused by absorption but can be due to instabilities in the accretion stream. The typical dip duration, of about 1000 s, is much longer than the time-scale attributed to the accretion of the clumpy stellar wind of the massive donor star, but is similar to the viscous time-scale at the inner radius of the accretion disc.